Extraction And Solubility Studies Of Virgin Coconut Oil From Coconut (Cocos Nucifera) Flesh Using Supercritical Carbon Dioxide - Setianto, Wahyu Bahari (2011)

(untitled)
Coconut (Cocos nucifera) oil which is extracted from fresh coconut flesh is known as virgin coconut oil (VCO). The oil is a natural source of medium chain tryglycerides (MCTs) which has been well known as healthy oil. It is remarkable that very few reports on the extraction of the VCO using SC-CO2 have been published hitherto the fundamental insights on the SC-CO2 extraction processes of the coconut oil are much lacking. The objectives of this work are evaluating the parameters effects of VCO extraction using SC-CO2 and examination of the oil solubility in SCCO2.